Antioxidative myricetin-enriched nanoparticles towards acute liver injury. Issue 38 (12th September 2022) - Wang, Tianyou; Zhang, Jianhua; Zhang, Hengjie; Bai, Wanjie; Dong, Jinhong; Yang, Zhen; Yang, Peng; Gu, Zhipeng; Li, Yiwen; Chen, Xianchun; Xu, Yuanting
Abstract : This manuscript developed myricetin-enriched nanomaterials with antioxidative abilities and therapeutic effects towards ALI, which could promote antioxidative nanomaterial development with naturally occurring molecules against intractable diseases. Abstract : Acute liver injury (ALI) could severely destroy the liver function and cause inevitable damage to human health. Studies have demonstrated that excessive reactive oxygen species (ROS) and accompanying inflammatory factors play vital roles in the ALI disease. Herein, we fabricated a kind of nature-inspired myricetin-enriched nanomaterial via Michael addition and Schiff base reaction, which possessed uniform morphology, tunable component ratios, great stabilities, promising free radical scavenging abilities, biocompatibility and protective effects towards cells under oxidative stress. Additionally, the therapeutic effects were demonstrated using an ALI model by down-regulating ROS and inflammatory levels and restoring the liver function. This study could provide a strategy to construct robust and antioxidative nanomaterials using naturally occurring molecules against intractable diseases.